1986
DOI: 10.1104/pp.81.4.1044
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Betaine on Enzyme Activity and Subunit Interaction of Ribulose-1,5-Bisphosphate Carboxylase/Oxygenase from Aphanothece halophytica

Abstract: The presence of betaine, a quaternary ammonium compound, at a concentration (0.5 molar) reported to accumulate inside Aphanothece halophytica in response to increasing external salinity, slightly promoted ribulose-1,5-bisphosphate (RuBP) carboxylase activity. KCI at 0.25 molar inhibited RuBP carboxylase about 55%. Betaine relieved the inhibition by 0.25 M KCI and the original uninhibited activity was restored at 1 M betaine. Other osmoregulatory solutes such as sucrose and glycerol also reduced KCI inhibition,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
43
0

Year Published

1988
1988
2003
2003

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 101 publications
(45 citation statements)
references
References 24 publications
1
43
0
Order By: Relevance
“…Betaine appears to be far less inhibitory to protein synthesis in vitro in comparison to inorganic ions of equivalent concentration (1, 4), and this type of evidence supports the notion that betaine accumulation is more compatible with cytoplasmic functions than accumulation of inorganic ions as cytoplasmic osmotica (27). Glycinebetaine is reported to have stabilizing effects on proteins at high temperatures (12,18).…”
mentioning
confidence: 99%
“…Betaine appears to be far less inhibitory to protein synthesis in vitro in comparison to inorganic ions of equivalent concentration (1, 4), and this type of evidence supports the notion that betaine accumulation is more compatible with cytoplasmic functions than accumulation of inorganic ions as cytoplasmic osmotica (27). Glycinebetaine is reported to have stabilizing effects on proteins at high temperatures (12,18).…”
mentioning
confidence: 99%
“…These compounds should, by definition, be non-toxic at high concentrations to cytoplasmic functions (Wyn Jones & Storey 1981), allowing turgor maintenance and/or protection of macromolecular structures (e.g protein folding or membrane stability) against the destabilizing effect of the decrease in water activity (Stewart & Lee 1974). Nevertheless, this 'protection' concept is essentially based on indirect evidence from in vitro experiments, such as the recovery of catalytic activities of enzymes inhibited by NaCl (Incharoensakdi, Takabe & Akazawa 1986;Solomon etal. 1994).…”
Section: Introductionmentioning
confidence: 99%
“…the destabilizing effects of chaotropic agents such as NaCl (Manetas 1990) or KCl (Incharoensakdi, Takabe & Akazawa 1986) as well as against thermal inactivation (Nikolopoulos & Manetas 1991;Arakawa & Timasheff 1985). However, these kinds of experiment do not integrate the functions of membranous systems, especially those concerned with the transduction of energy in chloroplasts and mitochondria.…”
mentioning
confidence: 99%
“…halophytica is an oxygen-evolving halotolerant cyanobacterium that can grow in a wide range of salinity conditions from 0.25 to 3.0 M NaCl concomitant with the accumulation of betaine (14,20). Previous studies have shown that A. halophytica has unique systems to survive under severe environmental conditions (20 -24).…”
mentioning
confidence: 99%
“…Previous studies have shown that A. halophytica has unique systems to survive under severe environmental conditions (20 -24). Ribulose-1,5-bisphosphate carboxylase/oxygenase of A. halophytica dissociates easily into large and small subunits when betaine was absent (20). A. halophytica DnaK has been shown to contain the longer C-terminal segment than other DnaK/Hsp70 family members (21) and exhibit extremely high protein folding activity at high salinity (22).…”
mentioning
confidence: 99%